Atención con calidad del aborto incompleto no complicado: aspiración manual endouterina comparada con legrado uterino instrumentado. hospital belén. hospital belén de Trujillo, 2006 – 2007 - Aldave Paredes, Pedro Gabriel (2009)
To determine if manual vacuum aspiration (MVA) is higher quality than uterine curettage (UC) in the management of uncomplicated incomplete abortion, specifying clinical differences and quality indicators and cost between both of techniques It was made a prospective study involving 252 patients with uncomplicated Incomplete abortion treated in the Obstetrics and Gynecology Department of Hospital Belen of Trujillo included randomly in the MVA and UC group respectively. It was registered the existence of complications, and it was offered to all patients counseling and contraception. At discharge, the patient was cited in 10 days and if she didnt return, home visit was made. In both procedures it was a predomination of sedation + analgesia. The pain intensity was higher in the MVA group . The Bleeding was higher in the UC group . Complications were higher in the UC group. however these werent statistically significant. The average hospital stay was higher in patients with UC. The average cost was S /. 167.67 for UC and 114.60 for MVA. 100% of them received counseling and 82% chose contraceptive method being the most request medroxiprogesterone (42.4%), IUD (25.7%) and the pìll (18.6%). Conclusions: MVA is higher quality than UC. Postabortion period is a good time for the administration of contraceptive methods.